Societe anonyme des pecheries Iraniennes, (p.4a) - Farid-Pak, F. (Electronic version published by Vancouver Island University, 1958)
Coloured print of 3 fish: "1-Grand Esturgeon (Beluga) -/Huso huso (L)/m"; "2-Esturgeon (OSCIETRE) - /Acipenser gulden stadti persicus Bor./"; 3-Esturgeon Stellifie (SEVRUGA) - /Acip. stel. n. Cyrensis Berg./" Print is part of an advertising booklet for a company in the Iranian fishery that produces caviar. From the collection of Gord Edmondson